Effect of sequential pre-treatment on the thermal behavior of pre-treated palm empty fruit bunch using thermal gravimetric analyzer / Nur Nasulhah Kasim ... [et al.] - Kasim, Nur Nasulhah; Mohamed, Alina Rahayu; Mohd Ishak, Mohd Azlan; Ahmad, Razi; Ali, Siti Nurlia; Ismail, Khudzir (Research Management Institute (RMI), 2024)
Utilizing sequential pre-treatment of demineralization and torrefaction on biomass prior to pyrolysis has shown to be promising in enhancing the solid fuel feedstock properties. The aim of this study is to further investigate the suitable biomass feedstock for the pyrolysis process by monitoring the thermal degradation behaviors of different pre-treated palm empty fruit bunch (PEFB) prior to pyrolysis process. Thermal analyses of all samples were performed using a Mettler Toledo TGA at a heating rate of 20 °C·min−1 with nitrogen flow of 100 mL·min−1 from ambient temperature to 900 °C. The thermogravimetric analysis displayed that the torrefied demineralised palm empty fruit bunch (TDPEFB) has experienced major weight loss of 61.53% at its active degradation temperature. Meanwhile, torrefied palm empty fruit bunch (TPEFB) showed a lower amount of weight loss compared to TDPEFB since the presence of alkali and alkaline earth metal (AAEM) in TPEFB which inhibits the primary reaction, thus leading to the retention of mass in the biochar fraction. In comparison, the percent weight loss for untreated PEFB was recorded to be the lowest among the three samples which is about 33.9% during the active pyrolysis process. The results support the argument that the demineralization process has assisted primary reactions by the removal of AAEM. This in turn contribute to higher weight loss of sample as more volatile matters and cellulose content could be released during thermal degradation of the TDPEFB. Subsequently, the quality and quantity of bio-oil produced could be enhanced. This sequential pre-treatment was suggested to be an effective approach for upgrading the quality of solid fuel feedstock for further thermal conversion processes such as pyrolysis.